Self-tensioning long-span T-shaped spruce and oak web floors with a CLT upper flange. An experimental approach. (1st August 2018) - Martín-Gutiérrez, E.; Estévez-Cimadevila, J.; Otero-Chans, D.; Suárez-Riestra, F.
Graphical abstract: Highlights: A self-tensioned system was developed to design small depth and long-span timber floors. The device automatically apply a post-tensioned force in reponse to gravitational loads. The T-shaped floors showed a noticeable reduction in their average relative deflection.